IMPROVING BUSINESS QUALITY THROUGH MANAGEMENT TRAINING AND MARKETING STRATEGIES - Siti Mariam; Irwan Sugiarto; Retno Wulansari; Eko Cahyo Mayndarto; Rudi Ginting; Noryani Noryani (International Journal of Engagement and Empowerment, 2022)
Competition in the business world is getting tighter along with the growth of a region or country.  Likewise, business activities in the Clothing industry are  also getting tighter and tighter. In the  Bandung area, there are clothing industry centers, all of which are  MSME artisans. In MSMEs, the weakness that  has always been owned is its  management and marketing strategy.  In this article, what  is discussed and done is to improve the  business ability of MSMEs by conducting  management training and marketing strategies.  This activity is also given knowledge on how to make Clothes that conform to  national standards.  There  are   2 forms of management training and marketing strategies that aim to improve the quality of their business.   This activity  aims to improve the  ability of clothing artisans in making quality clothing as one of  the marketing strategies